2010
DOI: 10.1007/s00198-010-1238-x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of smoking on bone mineral density and bone metabolism in elderly men: the Fujiwara-kyo Osteoporosis Risk in Men (FORMEN) study

Abstract: The impact of smoking on bone status is mainly associated with the number of smoking years in elderly men.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
40
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(51 citation statements)
references
References 29 publications
5
40
1
Order By: Relevance
“…The results of this large research support associations of previous studies among age, weight, height, BMI, and BMD in males (Cheng et al, 2012). Felson, Zhang, Hannan, and Anderson (1993), Malabanan et al (2013), and Tamaki et al (2011) indicated that low Note. BMD = bone mineral density; BMI = body mass index; OST = osteoporosis self-assessment tool; OR = odds ratio; CI = confidence interval.…”
Section: Discussionsupporting
confidence: 88%
“…The results of this large research support associations of previous studies among age, weight, height, BMI, and BMD in males (Cheng et al, 2012). Felson, Zhang, Hannan, and Anderson (1993), Malabanan et al (2013), and Tamaki et al (2011) indicated that low Note. BMD = bone mineral density; BMI = body mass index; OST = osteoporosis self-assessment tool; OR = odds ratio; CI = confidence interval.…”
Section: Discussionsupporting
confidence: 88%
“…Some previous studies have shown negative correlation between history of smoking and BMD in elderly men [29,30]. However, we could not find a relationship between smoking and bone loss in our study.…”
Section: Discussioncontrasting
confidence: 83%
“…[23][24][25][30][31][32][33] They also expected to find associations between oral tori and treatment with pharmacologic agents known for their bone-stimulating properties, such as antihypertension medications. [34][35][36] These investigations examined dental factors, TMD, and systemic factors, including treated hypertension, 36,34 treated hypothyroidism, [37][38][39][40] smoking, [41][42][43] periodontal disease, 44 treated diabetes mellitus, 45,46 penicillin allergy, [47][48][49] and treated anxiety/depression. [50][51][52] Research has linked each of these systemic factors with alterations in bone metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…[50][51][52] Research has linked each of these systemic factors with alterations in bone metabolism. 12,[36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54] Other factors studied included age, gender, and respiratory problems (asthma and obstructive sleep apnea).…”
Section: Discussionmentioning
confidence: 99%